Effect of pH on flux and rejection for diglycolamine and triethanolamine - Abidin, M.U.S.Z. (Italian Association of Chemical Engineering - AIDIC, 2015)
One of the solutions to reduce global warming is controlling carbon dioxide (CO2) emission to the atmosphere. Therefore, CO2 that contains in raw natural gas should be removed. Practically, alkanolamine solvent is used to capture CO2 in raw natural gas. During that process a volume of amines losses in some unit operations caused amines discharged into wastewater having higher chemical oxygen demand (COD). Due to that reason, amines wastewater must be treated prior discharge into the water body. Thus membrane was used to treat the wastewater with different adjusted pH to identify which pH gives better performance for nanofiltration membrane especially. The objectives of this study are to investigate the flux and rejection of two different types of amines called diglycolamine (DGA) and triethanolamine (TEA) across AFC40 membrane, and to evaluate the effect of feed pH on flux and rejection performance for this membrane against various types of amines. The experimental study was conducted to evaluate permeate flux and rejection of amines wastewater using nanofiltration AFC40 membrane at constant feed concentration (5000 mg/L) yet different pH (pH 3 and pH 8) solution. Samples taken from permeate flux study was used for rejection study where the samples was analysed using Standard Method 5220D closed reflux (colorimetric) method. The COD of those samples was measured by HACH DR5000 spectrophotometer at 620 nm. Experimental study showed that DGA obtained higher flux than TEA. This is because lower molecular weight of DGA gave it an advantage to diffuse faster through the membrane due to lesser resistant. Conversely, TEA achieved higher rejected amine compared to DGA. This can be clarified by molecular weight of amines. As TEA (149.19 g/mol) has higher molecular weight than DGA (105.14 g/mol), therefore TEA experienced greater sieving effect that maximised the surface resistant. Hence, higher rejection of TEA produced. Besides that, this study also found that DGA and TEA able to obtain higher flux at pH 8 compared to pH 3. This is because, AFC40 was made from polyamide which contains carboxyl and amine group at the surface which induced positive surface charged due to amine protonation in acidic solution and negative surface charged owing to deprotonation of carboxyl group in alkaline solution. The result showed that the membrane surface rich in carboxyl group at high pH. Therefore deprotonation of carboxyl group caused membrane surface become hydrophilic and looser skin thus higher flux can be gained. On the other hand, pH 3 amines solutions obtained higher rejection than pH 8 solutions. Due to the lone pair electron on nitrogen atom conquered by DGA and TEA, both solutions are actually basic and easily protonated by strong acid thus these solutions turned into positively charged solutes. As membrane surface also induced positive charged at that condition, electrostatic repulsion interaction between solute and membrane resulted in higher rejection for acidic solution. It can be conclude that AFC40 membrane exhibited positive charged at pH 8 and negative charged at pH 3. The result showed that pH variation plays significant role on membrane performance. Overall of this study, pH 3 of TEA showed good observed rejection behaviour towards AFC40 membrane. Copyright Â© 2015, AIDIC Servizi S.r.l.,.